CASES OF POLYSEMY AND SYNONYMY OF HIEROGLYPHIC COMPOUNDS - N. M. Berdikulova (International Journal of Literature and Language Studies, 2026)
This article examines the phenomena of polysemy and synonymy in Japanese kanji compounds. It analyzes their semantic characteristics, contextual usage, and their role within the lexical system of the language. Special attention is paid to processes of semantic extension as well as stylistic and pragmatic differences within synonymic sets.